2018
DOI: 10.1021/acs.jpcc.8b09361
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of 2H-MoSe2 by 3d Transition-Metal Doping

Abstract: To develop MoSe 2 -based photocatalysts, increasing the catalytic activity of 2H-MoSe 2 is essential. In this work, the electronic and photocatalytic properties of 3d transition metal-doped (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn) 2H-MoSe 2 were investigated by first-principles calculations. The results indicate that Sc, Ti, V, Cr, Mn, Fe, and Co atoms tend to substitute the Mo atoms under a Se-rich condition, whereas Ni, Cu, and Zn atoms prefer to occupy the interstitial positions. More importantly, Scand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Ab initio density-functional theory (DFT) simulations by Zhang et al. and Luo et al have shown that it is energetically favorable for Al to occupy a Mo site. , On the other hand, extrapolating the DFT simulations by Zhao et al for Sc through Zn doping of the related MoSe 2 would suggest that Al could occupy an interstitial site . It is not straightforward to determine the doping efficiency as it is not yet known how Al dopes with MoS 2 combined with the fact that Al can assume different dopant multiplicities (from Al 1+ up to the Al 3+ state). , However, the simplest scenario of Al acting as a 1-fold acceptor seems unlikely based on a carrier density of 10 21 cm –3 and an Al density of 5 × 10 20 cm –3 (estimated using the known Mo density of MoS 2 and the atomic percentage of Al, as measured by XPS).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ab initio density-functional theory (DFT) simulations by Zhang et al. and Luo et al have shown that it is energetically favorable for Al to occupy a Mo site. , On the other hand, extrapolating the DFT simulations by Zhao et al for Sc through Zn doping of the related MoSe 2 would suggest that Al could occupy an interstitial site . It is not straightforward to determine the doping efficiency as it is not yet known how Al dopes with MoS 2 combined with the fact that Al can assume different dopant multiplicities (from Al 1+ up to the Al 3+ state). , However, the simplest scenario of Al acting as a 1-fold acceptor seems unlikely based on a carrier density of 10 21 cm –3 and an Al density of 5 × 10 20 cm –3 (estimated using the known Mo density of MoS 2 and the atomic percentage of Al, as measured by XPS).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDs), such as MoSe 2 and WSe 2 , are promising candidates in novel high-performance nanoelectronic and optoelectronic devices due to their alluring properties. In general, intrinsic defects and unintentional impurities during the growth of the materials are unavoidable, and they dramatically affect the physical and chemical properties of the materials. On the other hand, the functionality of semiconductors depends essentially on whether enough free carriers can be introduced by doping. , Therefore, the prerequisite for designing and optimizing high-performance devices is to have deep understanding of the properties of defects in materials.…”
Section: Introductionmentioning
confidence: 99%
“…Chemie semiconducting 2D TMDs could bring various attractive advantages for photocatalytic application. [129][130][131][132][133] Theoretical calculation shows that the generated defect levels caused by the introduction of heteroatoms can adjust the band gaps of 2D TMDs, thereby tuning their redox ability. [129,130] Subsequent experimental studies confirmed this.…”
Section: Methodsmentioning
confidence: 99%